2015
DOI: 10.1556/650.2015.30158
|View full text |Cite
|
Sign up to set email alerts
|

Szorongás, depresszió, egészségkontrollhit és az egészség-magatartással való kapcsolatuk ischaemiás szívbetegek körében

Abstract: Bevezetés: Az ischaemiás szívbetegség vezető haláloknak számít hazánkban. Kialakulásában és a betegség prognózisá-ban is kiemelkedő szerepet játszanak a mentális és az életmódbeli tényezők. Célkitűzés: Ischaemiás szívbetegek kö-rében a szorongás, a depresszió és az egészséggel kapcsolatos kontrollérzés, valamint az egészség-magatartások ösz-szefüggéseinek elemzése. Módszer: Keresztmetszeti vizsgálatban 116 kardiológiai rehabilitációs osztályon fekvő beteg vett részt (56,9% férfi , átlagéletkor: 57,65±8,22 év).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
(49 reference statements)
0
4
0
3
Order By: Relevance
“…The prevalence of unmet medical needs has been found to be higher among those with worse mobility or with chronic pain due to the resultant difficulties with mobility [43]. Past studies have also found unmet medical needs to be associated with worse self-rated health status [44] and depression [45,46] because of the costs related to depression [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of unmet medical needs has been found to be higher among those with worse mobility or with chronic pain due to the resultant difficulties with mobility [43]. Past studies have also found unmet medical needs to be associated with worse self-rated health status [44] and depression [45,46] because of the costs related to depression [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…With chronic patients, in addition to adherence, the locus-of-control belief can also be crucial for further improvement of health status 39. Internal control has a positive effect on the health behavior of the patient;40 it may influence which health-related behaviors a person will prefer or perform during diabetes therapy 41. However, a lack of internal control may lead to unhealthy dietary choices among people with diabetes 42.…”
Section: Introductionmentioning
confidence: 99%
“…Eredményeik igazolták a pszichodiagnosztika és szükség esetén a személyre szabott pszichológiai és/vagy pszichiátriai beavatkozás (pszichoedukáció, kognitív viselkedéses terápia, gyógyszeres terápia stb.) szükségességét a szívbetegek körében [46].…”
Section: Pszichoszociális Kezelésunclassified